A coordinated national UK liver transplant program response, prioritizing waitlist recipients with the highest need, provided excellent outcomes during the first wave of the COVID‐19 pandemic. Issue 4 (6th January 2022) - Masson, Steven; Taylor, Rhiannon; Whitney, Julie; Adair, Anya; Attia, Magdy; Gibbs, Paul; Grammatikopoulos, Tassos; Isaac, John; Marshall, Aileen; Mirza, Darius; Prachalias, Andreas; Watson, Sarah; et al.
Abstract: Introduction: Healthcare provision has been severely affected by COVID‐19, with specific challenges in organ transplantation. Here, we describe the coordinated response to, and outcomes during the first wave, across all UK liver transplant (LT) centers. Methods: Several policy changes affecting the liver transplant processes were agreed upon. These included donor age restrictions and changes to offering. A "high‐urgency" (HU) category was established, prioritizing only those with UKELD > 60, HCC reaching transplant criteria, and others likely to die within 90 days. Outcomes were compared with the same period in 2018 and 2019. Results: The retrieval rate for deceased donor livers (71% vs. 54%; P  < .0001) and conversion from offer to completed transplant (63% vs. 48%; P  < .0001) was significantly higher. Pediatric LT activity was maintained; there was a significant reduction in adult (42%) and total (36%) LT. Almost all adult LT were super‐urgent ( n  = 15) or HU ( n  = 133). We successfully prioritized those with highest illness severity with no reduction in 90‐day patient ( P  = .89) or graft survival ( P  = .98). There was a small (5% compared with 3%; P  = .0015) increase in deaths or removals from the waitlist, mainly amongst HU cohort. Conclusions: We successfully prioritized LT recipients in highest need, maintaining excellent outcomes, and waitlist mortality was only marginally increased.